Education for all in Bangladesh : Where does Bangladesh Stand in Terms of Achieving the EFA Goals by 2015? - World Bank (Washington, DC, 2012)
The objectives of this policy note are twofold: first, take stock of where Bangladesh stands in terms of achieving the Education For All (EFA) goals; and second, suggest policy recommendations that could help Bangladesh to meet the EFA goals by 2015. The policy note will focus mainly on: 1) universal primary enrollment for all children; 2) universal primary completion; 3) gender parity in education; 4) adult literacy; and 5) quality of education. This is because these areas can be more meaningfully analyzed with reasonably reliable information from various sources. Bangladesh is unlikely to achieve universal primary enrollment and completion by 2015 if the current trends in access and completion do not improve. Progress in school quality is more difficult to assess because of the lack of systematic assessment and monitoring of learning achievement results. The government continues to be the main provider and financer of primary education. Improving the overall quality of schooling is a pressing task in order to substantially raise enrollment and help more children complete primary school with the appropriate skills in literacy and numeracy. Bangladesh has made progress towards increasing both primary and secondary enrollment and has already reached gender parity in both education levels.